The safety of authenticity: Ali Kebab, or an exploration in the contemporaneity of foreignness and the self's post-colonial imaginary. (June 2013) - Barras, Amélie; Guillaume, Xavier
The article explores how the concept of authenticity is deployed in contemporary Switzerland to delimit not only the representational boundaries of the Muslim (foreign) 'other', but also of the dominant cultural self. The authors analyse the act of constituting the authentic other in relation to the stability, comfort and safeness of the dialogically constituted authentic self, as illustrated in a Swiss advertising campaign in summer 2009. To investigate how those power relations unfold in the Ali Kebab advertising campaign, the article draws on a framework of visual analysis that studies the field of significations carried by specific images in relation to the particular context in which they are deployed, then facilitates their recontextualisation within wider social discourses. This sheds light on how the categories of authenticity displayed by the Ali Kebab adverts draw on a deep and powerful colonial imaginary that goes well beyond the borders of Switzerland.